Asymmetric Wars: Origin and Evolution (قضايا سياسية, 2022)
The difference in the patterns of war is not a new phenomenon, as it indicates throughout history that there is a noticeable difference in it, as it refers to the nature of the difference and development in the military capabilities and strategy of the warring countries, and that this difference and development is mainly due to the nature of "war" Something of a subjective nature and an objective nature. This change was reflected in the nature of the solution on the subjective nature and not the set nature, because war is war, but the modes of its waging are changing and evolving, and it is recognized that the war is often between two similar parties, then it is called war: symmetrical, or regular If its two sides are states, or it may be called “asymmetric war”, “irregular war”, or “asymmetric war”, as if one of its parties is non-state, in which a representative from “non-state” is usually used, Also, "asymmetric" methods are used, to target the vulnerabilities of "countries" to achieve a disproportionate effect. In this research, we will discuss the concept and philosophy of "asymmetric wars", and then the historical rooting and development of "asymmetric wars", their types, and a statement of the concepts close to them, and their characteristics, in a way that enables us later to know the formula of those wars in our world today, as an "asymmetric war". It is not subject to the rules of “regular war,” by virtue of the fact that one of its two sides is an entity other than the state, and that most of its fields are not identical battlefields.